Multipath Routing Algorithm to find Optimal Path in SDN with POX Controller - Goteti, Deepthi; Rasheed, Imran (International Journal of Electrical and Computer Engineering Systems, 2025)
The past decade witnessed a tremendous increase in network usage, and traditional network architecture is needed to sustain modern requirements with high throughput and minute delay. This leads to the introduction of software-defined networks. Congestion is a critical problem that needs attention, so identifying the optimal path is required to eliminate the congestion. Researchers introduce rigorous studies to identify optimal paths, some resulting in less data loss and delay. Identifying multiple paths between nodes may eliminate congestion. When the first best path is congested, selecting the second best path between nodes can solve the congestion problem. With this ideology, the multipath routing algorithm is developed and tested on Fat Tree, Custom, and Tree topologies, and performance is measured using quality of service factors. Considering Throuhput, Fat Tree produced 27.15% better throughput than the tree topology and 17.57% better than the custom topology, Whereas in the case of jitter, fat tree topology reduces jitter by about 90.36%compared to the tree topology, but custom topology reduces jitter by about 12.24% compared to the fat-tree topology. In the packet delivery ratio, fat tree topology reduces packet loss by about 77.87% compared to the tree topology. Fat tree topology reduces packet loss by about 55.62% compared to the custom topology. Fat tree performs best overall, with the highest throughput, lowest packet loss, and significantly reduced jitter compared to the tree and custom topologies.MiniNet is used to perform simulations. TCP and UDP flows are calculated with the iperf tool and tested on the POX Controller.